2019
DOI: 10.1002/ece3.5632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human‐induced prey depletion on large carnivores in protected areas: Lessons from modeling tiger populations in stylized spatial scenarios

Abstract: Prey depletion is a major threat to the conservation of large carnivore species globally. However, at the policy‐relevant scale of protected areas, we know little about how the spatial distribution of prey depletion affects carnivore space use and population persistence. We developed a spatially explicit, agent‐based model to investigate the effects of different human‐induced prey depletion experiments on the globally endangered tiger (Panthera tigris) in isolated protected areas—a situation that prevails thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Rising anthropogenic impacts increase pressure on species interactions through the loss of complex carnivore guilds, declines in natural prey, and shrinking protected area networks (Jones et al., 2018; Sévêque et al., 2020). These factors can distort carnivore dynamics and ecosystem function through increased competition for resources (Creel et al., 2018; Manlick & Pauli, 2020), reduced suppression of mesocarnivores (Brook et al., 2012; Prugh & Sivy, 2020), shifts in spatial use (Carter et al., 2019; Parsons et al., 2019), and changes in survival rates for dominant and subordinate competitors (M’soka et al, 2016; Elbroch & Kusler, 2018). These alterations in community assemblage and species dynamics can result in cascading trophic effects (Finke & Denno, 2005; Suraci et al., 2016; Winnie & Creel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rising anthropogenic impacts increase pressure on species interactions through the loss of complex carnivore guilds, declines in natural prey, and shrinking protected area networks (Jones et al., 2018; Sévêque et al., 2020). These factors can distort carnivore dynamics and ecosystem function through increased competition for resources (Creel et al., 2018; Manlick & Pauli, 2020), reduced suppression of mesocarnivores (Brook et al., 2012; Prugh & Sivy, 2020), shifts in spatial use (Carter et al., 2019; Parsons et al., 2019), and changes in survival rates for dominant and subordinate competitors (M’soka et al, 2016; Elbroch & Kusler, 2018). These alterations in community assemblage and species dynamics can result in cascading trophic effects (Finke & Denno, 2005; Suraci et al., 2016; Winnie & Creel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This could be an outcome of several factors in combination. Numerous studies have demonstrated that the spatial distribution of predators is primarily affected by the spatial distribution of their wild prey (Carter et al, 2019). For instance, prey densities are the key determinant for tiger presence across a 38,000 km 2 landscape in Southern India (Karanth et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies of foraging behaviour and available prey for tigers in the Terai Arc Landscape, with recommendations to restore prey populations in the region (e.g. Basak et al, 2018; Carter et al, 2019; Dorji et al, 2019).…”
Section: Synthesis and Interpretationmentioning
confidence: 99%